Digital tools for assessing disease severity in dermatology - Khushboo H Modasia; Feroze Kaliyadan (Wolters Kluwer Medknow Publications, 2022)
Innumerable scoring systems have been introduced to measure the disease severity of various dermatological conditions. The development of such scores has proved to be beneficial to assess disease progression and treatment effectiveness in the context of dermatological research. However, these scoring systems tend to be time consuming, monotonous, and hence often difficult to use during overburdened routine clinical consultations, especially when it is in the form of a paper-based system. Many of the scoring systems are now available in the digital form, such as smart phone apps. This aids to calculate effortlessly and reduces human errors associated with paper-based formats. Various calculators like Psoriasis Area Severity Index calculators, Severity Scoring Of Atopic Dermatitis, and Melasma Area Severity Index have been introduced in the digital format for a quicker, efficient quality of work and uncomplicated data storage. This review highlights and discusses some of the digital tools available at present for severity scoring in dermatology.